Persepsi dan Motivasi Dalam Memilih Perumahan (Studi Kasus: Perumahan Villa Citra dan Villa Buana Garden) - Edi Mawardi; Rinaldy Rinaldy (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
In addition to being the center of Aceh's administrative administration, Banda Aceh is also the center of economic, educational and trade activities, so that economic growth and the population grow rapidly. Consumer factors in choosing housing vary greatly, because each individual has different desires in choosing the desired housing. The purpose of this study is to find out consumer factors in choosing and determining the desired housing. Based on the theories and views outlined, a resume can be made about consumer preferences in choosing and determining residence/housing. The results of the conclusion analysis of 100 respondents kept Villa Citra housing 39.02% age <30 years and 26.83% aged> 51 years while in Villa Buana housing 42.37% were aged 31-40 years. The two houses were complying with the Bachelor degree educational background, namely: 60.98% Villa Citra and 67.80% Villa Buana. analysis that 43.90% earned IDR 1,000,000 - 2,500,000 chose Villa Citra housing because of the influence of the distance to the city center of about 3.5 Kilometers. while Villa Buana reached 61.02% with an income of IDR 2,500,001 - 4,000,000 with an urban center of around 5.5 Kilometers.